PELATIHAN PEMBUATAN KOMPOS ORGANIK CAIR DARI URIN SAPI TERHADAP PEMUDA DI DESA PEBAUN HULU - Marlina, Gusti; Desta Andriani; Elfi Indrawanis; Tri Nopsagiarti; Chairil Ezward; Wahyudi; A.Haitami (Fakultas Pertania Universitas Muara Bungo, 2024)
Cow urine waste is unused waste that is still scattered in Pebaun Hulu village, Kuantan Mudik District, Kuantan Singingi Regency. Currently, cattle waste, especially urine, causes environmental pollution, which disrupts people's comfort. This community service activity aims to train the community, especially the youth of Pebaun Hulu village, to utilize cow urine into liquid organic fertilizer (POC) using fermentation techniques with EM-4. The target of the training activities is the youth of Pebaun Hulu village. Training activities were carried out over two meetings. Based on the pre-test results, 80% of youth do not understand the benefits of fertilizer and do not understand how to make POC. The method used in the training consists of three stages, namely lecture, discussion and practice. The result of the training is that the youth of Pebaun Hulu village understand and understand how to make POC from cow urine found in their environment using the EM-4 fermentation technique. Through this activity, it has also changed the paradigm of the people of Pebaun Hulu village, Kuantan District, Kuantan Singingi Regency who consider cow dung as waste that can pollute the environment to be more useful.